2020
DOI: 10.12659/msm.922987
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Sum Analysis of the Operator Learning Curve for Robot-Assisted Mayo Clinic Level I–IV Inferior Vena Cava Thrombectomy Associated with Renal Carcinoma: A Study of 120 Cases at a Single Center

Abstract: Departmental sources Background:This study aimed to use cumulative sum analysis of the operator learning curve for robot-assisted Mayo Clinic level I-IV inferior vena cava (IVC) thrombectomy associated with renal carcinoma, and describes the development of an optimized operative procedure at a single center. Material/Methods:A retrospective study included 120 patients with Mayo Clinic level I-IV IVC thrombus who underwent robotic surgery between 2013 and 2018. Points in the learning curve were identified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Only 1 study reported on predictors of perioperative outcomes following R-CT. In a study of 120 cases, Shen et al identified greater thrombus length, a higher level of thrombus (III–IV), and early surgical learning phase (as defined by first 40 cases) to be independent predictors of operative time and blood loss in R-CT. 36 They also reported IVC wall resection (cavectomy), III–IV thrombus and an early surgical learning phase to be independent predictors of early postoperative complications.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Only 1 study reported on predictors of perioperative outcomes following R-CT. In a study of 120 cases, Shen et al identified greater thrombus length, a higher level of thrombus (III–IV), and early surgical learning phase (as defined by first 40 cases) to be independent predictors of operative time and blood loss in R-CT. 36 They also reported IVC wall resection (cavectomy), III–IV thrombus and an early surgical learning phase to be independent predictors of early postoperative complications.…”
Section: Resultsmentioning
confidence: 96%
“…Table 1 summarizes the various case reports and case studies reporting outcomes of R-CT. A total of 21 studies were included. 10,21–40 All the studies were published in English except for 1, for which an English translation was retrieved. 33 Eight (38.1%) of the 21 single-arm studies were case reports involving 1 or 2 patients, and 9 (42.9%) included more than 10 patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, our present results showed that there were no significant differences in operating time or blood loss between the cohorts. Our recent research on the LC of RA‐IVCTE also proved that the LC began to enter a stable improvement period after the initial 40 cases [38]. For level III–IV RA‐IVCTE the inflexion point would be delayed accordingly.…”
Section: Discussionmentioning
confidence: 97%
“…The multidisciplinary team in which the author works has accumulated a wealth of experience in using robotic surgery for this kind of tumor thrombus. Clinical practice prompts robot-assisted thrombectomy for high IVCTT to be safe and feasible [ 14 , 20 22 ]. Robotic surgery significantly reduces injury compared to the surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although robotic surgery has been proven to be technical feasible, there is a shortage of clinical reports [ 11 , 12 ]. Moreover, most of the articles focus on level III tumor thrombus, and only our center has reported on level IV tumor thrombus [ 2 , 13 , 14 ]. Most studies lack a detailed description of the operation technology and repeatability of the methods, especially in the high inferior vena cava dissociation, suspension, occlusion and thrombectomy.…”
Section: Introductionmentioning
confidence: 99%